Identification of molecular markers associated with kernel iron and zinc concentrations in groundnut (Arachis hypogaea L.) - K. Sadaiah; K. Radhika; V.L.N. Reddy and; V. Padma (Electronic Journal of Plant Breeding, 2017)
Micronutrient malnutrition affects more than one-half of the world’s population, especially women and pre-school children. Poor consumers in developing countries acquire roughly one-half of their total iron intakes and a higher percentage of zinc intakes from staple foods. Bio-fortification, an approach of breeding crop plants for higher micronutrient concentration, is a cost effective and sustainable solution for tackling the micronutrient deficiencies. Developing countries, where micronutrient deficiencies are widespread, contribute world’s maximum peanut area and production. Thus, peanut can contribute significantly towards reduction of protein-energy and micronutrient malnutrition. With the advent of molecular markers, by using segregating populations for the trait of interest for breeders, it has now become effective to map genes or Quantitative Traits Loci (QTLs) and identify valuable alleles for the corresponding traits. In the present study, an F2:3 mapping population derived from the cross ICGV 06099 × ICGV 93468 was genotyped using 33 polymorphic SSR markers to identify the putative genomic regions associated with the kernel iron and zinc concentrations in groundnut using Single Marker Analysis (SMA). Results revealed that three markers viz., SEQ1B09 (0.23 %), IPAHM245 (2.19 %) and SEQ9G05 (6.34 %) showed significant association with the kernel iron and three markers viz., GM2638 (1.75 %), IPAHM245 (2.25 %) and SEQ9G05 (6.01 %) showed significant association with kernel zinc concentration. Significant positive association (0.549) was observed between kernel iron and zinc concentrations. Validation of these markers in an alternate F2:3 population derived from the cross ICGV 06040 × ICGV 87141 also showed strong association of these markers with the traits of interest.